2015
DOI: 10.1590/1982-451320150111
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem geoestatística dos casos de dengue e da variação termopluviométrica em João Pessoa, Brasil

Abstract: RESUMO:A dengue é uma doença viral cujo número de casos aumentou consideravelmente nas últimas décadas em várias regiões do Brasil. ABSTRACT: Dengue is a viral disease whose incidence has increased considerably in recent decades. This study aimed to investigate the climatic factors associated with the incidence of dengue fever in the city of João Pessoa, Paraíba State, in the period between 2007 and 2011. The analysis has included thermo-rainfall collected in INMET, and the cases of dengue obtained in the Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
0
6
1
7
Order By: Relevance
“…Os resultados indicam que, em Porto Alegre, RS, a precipitação não influencia significativamente o número de fêmeas coletadas (p = 0,3505). A relação da precipitação com o número de fêmeas é bem clara em regiões do país onde as estações climáticas não são bem definidas, por exemplo, estudos apontam associação entre os casos de dengue com a precipitação em unidades geográficas da Paraíba (Silva et. al., 2015, Almeida e Silva, 2017.…”
Section: Resultsunclassified
“…Os resultados indicam que, em Porto Alegre, RS, a precipitação não influencia significativamente o número de fêmeas coletadas (p = 0,3505). A relação da precipitação com o número de fêmeas é bem clara em regiões do país onde as estações climáticas não são bem definidas, por exemplo, estudos apontam associação entre os casos de dengue com a precipitação em unidades geográficas da Paraíba (Silva et. al., 2015, Almeida e Silva, 2017.…”
Section: Resultsunclassified
“…The relationship between the levels of this variable and dengue cases changes according to the place of study. In Boa Vista, RO, the correlation between the number of reported cases and the meteorological variables was not found, presenting a different pattern each year, highlighting the existence of case peaks in both the rainy and dry periods [21], in João Pessoa, PB, between 2007 and 2011, there was a greater number of records in the period in which there are higher precipitation values, corresponding to 85% of the notified cases [73], as well as, between 2007 and 2012, in Recife, PE, 1,844 cases of dengue were confirmed correlated to a pluviometric accumulation [74].…”
Section: Societal Response and Human Factormentioning
confidence: 93%
“…Some research in Brazil has shown the humidity variable as being relevant for the development of the denguecarrying mosquito and the incidence in the number of cases of the disease (Custódio et al, 2019;Correia, 2017;Degener et al, 2014;Silva et al, 2015). The degree of correlation of the NCPPDS and RHCA showed in Tab.4 reveals humidity as the variable with the greatest direct association with dengue, followed by precipitation, both showed a strong degree of relationship with each other since rainier days tend to be wetter.…”
Section: Bivariate Correlation Between Ncppds and Climate Variablesmentioning
confidence: 94%